2016
DOI: 10.1111/all.12860
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, 5‐arm dose finding study with a mite allergoid SCIT in allergic rhinoconjunctivitis patients

Abstract: In this mite allergoid SCIT dose finding study in HDM-induced ARC, concentrations of ≥20 000 AUeq/ml showed both immunological effects and clinical efficacy in the TNPT compared with placebo. The risk-benefit ratio favours 20 000 AUeq/ml and 50 000 AUeq/ml strengths for further clinical development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…In PQBirch204, the shape of the dose response curve showed that the highest dose of 27 300 SU was approaching a “plateau” (Figures and ). Nonmonotonic curves may occur with a sublingual immunotherapy (SLIT) and allergoid house dust mite SCIT . Further assurance about the reproducibility of this method of analysis is confirmed by the overlapping of the mean TSS scores from the PQBirch203 on the PQBirch204 MCP‐Mod dose response curves.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In PQBirch204, the shape of the dose response curve showed that the highest dose of 27 300 SU was approaching a “plateau” (Figures and ). Nonmonotonic curves may occur with a sublingual immunotherapy (SLIT) and allergoid house dust mite SCIT . Further assurance about the reproducibility of this method of analysis is confirmed by the overlapping of the mean TSS scores from the PQBirch203 on the PQBirch204 MCP‐Mod dose response curves.…”
Section: Discussionmentioning
confidence: 93%
“…Efficacy of allergen immunotherapy (AIT) is related to the cumulative dose (CD) of the allergen or allergoid for symptom control and immunological changes. No consensus exists on the best method to select the optimal effective and tolerable CD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allergen titration should be limited to research settings, therapy control (testing the response to certain treatments, if continuation of therapy needs to be decided), dose finding processes (to determine the sensitivity threshold of each allergen in research settings), or patients with extremely high grades of sensitization, in whom the standardized concentration might evoke anaphylaxis and asthma attacks …”
Section: Resultsmentioning
confidence: 99%
“…The safety profile of allergen immunotherapy (AIT) has been thoroughly documented in well-designed clinical studies (8)(9)(10) . Also, recently, the Immunotherapy Interest Group of the European Academy of Allergy and Clinical Immunology (EAACI)…”
Section: Discussionmentioning
confidence: 99%